Strengthening Maternal Health through Targeted Prenatal Class Promotion in Rural Indonesia - Wulandari, Ratna Dwi; Laksono, Agung Dwi (New Countryside, 2026)
Prenatal classes are a key component of antenatal health promotion, supporting maternal knowledge, confidence, and preparedness for childbirth. However, evidence on determinants of prenatal class participation in rural settings remains limited, particularly from nationally representative data. This study aimed to identify sociodemographic determinants of prenatal class participation among rural women in Indonesia and to examine geographic disparities. We analyzed secondary data from the 2023 Indonesian Health Survey, including 34,243 rural women who had given birth within the previous five years. Prenatal class participation was the dependent variable, while age, marital status, education, employment, household wealth, and parity were included as independent variables. Binary logistic regression was applied, accounting for survey weights, and spatial mapping was conducted to visualize provincial variation. Overall, 35.8 percent of rural women attended prenatal classes. Older age, being married, higher education, unemployment, and higher parity were associated with higher participation. Compared with the richest group, women in poorer and middle wealth categories were more likely to attend prenatal classes, while the poorest group showed no significant difference. Substantial regional disparities were observed, with the lowest participation concentrated in eastern Indonesia. This study advances the literature by combining nationally representative analysis with spatial mapping to highlight inequities in prenatal class participation in rural Indonesia. Targeted interventions are needed to reach adolescents, first-time mothers, employed women, and socially disadvantaged groups.